GAMBARAN PERBEDAAN PENGETAHUAN TENTANG ANEMIA SEBELUM DAN SESUDAH DIBERI PENYULUHAN PADA REMAJA PUTRI DI SMUN 5 KELAS XI-XII - Sari Pratiwi Apidianti; Emi Yunita (Universitas Islam Madura, 2021)
Iron deficiency anemia is the most common nutritional problem in the world and affects more than 600 million people. Knowledge about anemia is one of the causes of the low ability to cope with the symptoms of anemia. To overcome public knowledge which is still classified in the less category, it can be done by conducting counseling. The purpose of this study was to describe the difference in knowledge about anemia before and after being given counseling to young women at SMA 5 Class 1-2 Pamekasan in 2008. This research is a descriptive survey. The sample is 33 respondents with quota sampling technique that is equal to 25% of the population. The independent variable is counseling. The dependent variable is Knowledge about Anemia before and after counseling. Data were collected by questionnaires and counseling using the lecture method. Data analysis using frequency distribution test. The results showed that the description of the level of difference in knowledge of adolescent girls about anemia before and after being given counseling at SMUN 5 Pamekasan in 2008 in the good category increased by 24%. Therefore, it is necessary to conduct IEC (communication, information and education) about anemia to students to prevent the occurrence of anemia, especially when young women are menstruating.